2022
DOI: 10.1001/jamanetworkopen.2022.23236
|View full text |Cite
|
Sign up to set email alerts
|

Association of Problematic Anger With Long-term Adjustment Following the Military-to-Civilian Transition

Abstract: IMPORTANCE Few studies have examined the role of problematic anger in long-term adjustment of service members transitioning out of the military. OBJECTIVE To determine the prevalence of problematic anger during the military-to-civilian transition period and the association of problematic anger with adjustment to civilian life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Furthermore, navigating a new civilian life can involve economic challenges and workrelated struggle. Previous work has shown signi cant associations between problematic anger and economic dysfunction(Adler et al, 2022), thus the increased economic instability associated with changing career may partially account for the increased levels of anger among veterans in our study.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Furthermore, navigating a new civilian life can involve economic challenges and workrelated struggle. Previous work has shown signi cant associations between problematic anger and economic dysfunction(Adler et al, 2022), thus the increased economic instability associated with changing career may partially account for the increased levels of anger among veterans in our study.…”
mentioning
confidence: 54%
“…The relationship between military personnel entering the civilian world and the phenomenon of problematic anger is, however, relatively unexplored. In an exception, one study found signi cant associations between problematic anger during the transition and emotional, relational, and nancial functioning approximately 5 years later (Adler et al, 2022). Such ndings suggest the importance of considering the military-tocivilian transition in modeling risk of problematic anger.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only is problematic anger prevalent, it is associated with difficulties across psychosocial and economic domains. In studies of US military personnel, problematic anger has been associated with worse psychological health and challenges with personal relationships, parenting, financial well-being, employment, and housing, even after adjusting for co-occurring mental health problems . In addition, studies of Australian military personnel have identified that problematic anger from point of recruitment has a negative impact on mental health trajectories .…”
Section: Introductionmentioning
confidence: 99%
“…Anger is a basic human emotion that is experienced as a reaction to the unwanted or unexpected behavior of others and often occurs after traumatic experiences, frustrations, and stressful situations. Research suggests that military service and ex-service personnel commonly experience difficulties with anger and aggression (Adler et al, 2022; Adler et al, 2020; Rona et al, 2015; Turgoose and Murphy, 2018). In the United Kingdom (UK), prevalence estimates are approximately 29% for all types of physical aggression, 13% for violent behavior, and 10% for physical assault (MacManus et al, 2012; MacManus et al, 2015).…”
mentioning
confidence: 99%